ORCHIDS OF LONG BANGA - Rusea, Go; Edward Entalai, Besi; Siti Fatimah, Md Isa; Akmal, Raffi (2020)
A total of 150 specimens were collected from 6 sites (3 trails and 3 non-trails) in Long Banga forests and they were identified into 118 species. Most of the species documented were epiphytes including an endemic giant orchid, Dimorphorchis lowii and a member of the most appreciated orchid as agricultural crop, Vanilla cf. havilandii. In addition, 15 terrestrials and 3 saprophytes namely Aphyllorchis montana, Cystorchis stenoglossa and Gastrodia javanica were also documented during the study. Seventeen species were identified as new records for Sarawak.